The Representation of Women on Sixteenth-Century French Manuscript Maps of the World: Adornment, Enticement, and Admonition - Serchuk, Camille (The Cartographic Journal, 2025)
Keywords: Field (mathematics); Key (lock); Norman maps and atlases; Representation (politics); Rotz Atlas; Term (time); The Hague Atlas; Vallard Atlas; dept.art; map decoration; representation of women

À la limite: la vie et la carrière de Zacharie de Celers - Serchuk, Camille (La Picardie Flamboyante: Arts et reconstruction entre 1450 et 1550, 2015)
À la limite: la vie et la carrière de Zacharie de Celers
Keywords: dept.art

Silences in the Maps of Mercator: art, Science, and Faith - Serchuk, Camille (Gerhard Mercator: Wissenschaft und Wissenstransfer, 2015)
Die Projektion Gerhard Mercators setzte Maßstäbe in der Kartographie und wurde zum weltweiten Standard, bis sie im 20. Jahrhundert in die Kritik geriet und sukzessive abgelöst wurde. Dieser Band, hervorgegangen aus einer internationalen Tagung aus Anlass des 500. Geburtstags Mercators, nimmt den Gelehrten und sein Werk im Kontext mittelalterlicher und frühneuzeitlicher Diskurse, Netzwerke und Dimensionen der Wissensproduktion in den Blick. Am Standort Duisburg war Mercator auf Informationen aus aller Welt angewiesen, die er durch ein briefliches Kommunikationsnetz und über Vermittlung durch Abraham Ortelius erhielt. Der Selbstverlag, der auf der Mitarbeit der Familie basierte, produzierte und vertrieb das umfangreiche Werk, das weit mehr als Karten und Globen umfasste. Die Rezeption des Werks, die Nutzung und Popularisierung seiner Karten und Globen werden in diesem Band ebenso beleuchtet wie die Wirkung seiner wissenschaftlichen Erkenntnisse bis in unsere Gegenwart.
Keywords: dept.art

Illuminations in the Manuscripts of Alain Chartier - Serchuk, Camille (A companion to Alain Chartier (c. 1385-1430): father of French eloquence, 2015)
In Alain Chartier: Père de l'éloquence française contributors explore the diverse literary production of this influential late-medieval writer, whose concern with personal and political ethics and renovation of poetic form inspired generations of writers, and still resonate with modern readers.
Keywords: Chartier; Alain; active 15th century; Criticism and interpretation; Eloquence in literature; European; French; French literature; Histoire et critique; History and criticism; Jusqu'à 1500; LITERARY CRITICISM; Literature; Medieval; Littérature française; Littérature médiévale; To 1500; dept.art; Éloquence dans la littérature

Review of La Mappa mundi d’Albi: Culture géographique et représentation du monde au haut Moyen Âge - Serchuk, Camille (Imago Mundi, 2023)
_eprint: https://doi.org/10.1080/03085694.2023.2221560
Keywords: book.review; dept.art

Gregory T. Clark, Art in a Time of War: The Master of Morgan 453 and Manuscript Illumination in Paris during the English Occupation (1419–1435) - Serchuk, Camille (Speculum, 2019)
Keywords: book.review; dept.art

Review of Images, pouvoirs et normes [Review of the book Images, pouvoirs et normes: Exégèse visuelle de la fin du Moyen Âge] - Serchuk, Camille (H-France Review, 2019)
Keywords: book.review; dept.art; ⛔ No DOI found

Medieval Art in Motion: The Inventory and Gift Giving of Queen Clémence de Hongrie by Mariah Proctor-Tiffany (review) - Serchuk, Camille (French Studies: A Quarterly Review, 2020)
Keywords: book.review; dept.art

Review of Christian Maps of the Holy Land - Serchuk, Camille (The Medieval Review, 2022)
Keywords: book.review; dept.art; ⛔ No DOI found

Review of the book Visual Translation. Illuminated Manuscripts and the First French Humanists - Serchuk, Camille (H-France Review, 2023)
Keywords: book.review; dept.art; ⛔ No DOI found

Art, Accuracy and Agency in Georges Lallemant’s Map of Suresnes of 1619 - Serchuk, Camille (For a history of the local map at the end of the Middle Ages and the Renaissance, 2022)
Keywords: dept.art; ⛔ No DOI found

Viewing the Vilaine: illustration, illumination, and innovation in France, circa 1543 - Serchuk, Camille (Territoires, régions, royaumes. Le développement d’une cartographie locale et régionale dans l’Occident latin et le monde arabe (Xe-XVe siècle)., 2023)
Keywords: dept.art; ⛔ No DOI found

Quand les artistes dessinaient les cartes: vues et figures de l'espace français, Moyen âge et Renaissance [exposition, Paris, Hôtel de Soubise-Musée des Archives nationales, 25 septembre 2019-6 janvier 2020] - Dumasy-Rabineau, Juliette; Gastaldi, Nadine; Serchuk, Camille (le Passage Archives nationales, 2019)
Keywords: SCSU Faculty Scholar Award; award_winner; dept.art

Embroidered Lines and Cut Threads: Women's Domestic Needlework in the Italian Diaspora. - Inguanti, Joseph J. (2008)
Keywords: dept.art; faculty_collection; sabbatical_report

Realm and Representation: Art and Cartography in Late Medieval France. - Serchuk, Camille (2008)
Keywords: dept.art; faculty_collection; sabbatical_report

Hysterical Sustenance: A Painted Investigation into Nature and Artiface, Food and Still Life. - Brownell, Mia (2005)
Results from sabbatical resulted in grants, peer review and extensive exhibitions. Several paintings were done examining the traditions of food as a subject in still life using genetically modified food.
Keywords: dept.art; faculty_collection; sabbatical_report

Rome as a Work of Art and 17th Century Dutch Art. - Levine, David A. (2003)
Keywords: dept.art; faculty_collection; sabbatical_report

Ozias Blue and Me. - Carr, T. Wiley (Fall;Art., 2001)
Keywords: dept.art; faculty_collection; sabbatical_report

Italian-American Landscape of the New York-New England Region. - Inguanti, Joseph (2001)
Keywords: dept.art; faculty_collection; sabbatical_report

Pictorial Political Propaganda of the French Court in the Reign of Charles Vii, 1422-1461. - Serchuk, Camille (2001)
Keywords: dept.art; faculty_collection; sabbatical_report

The Human Element Within Societal Structures, Mixed Media Outdoor Sculptural Works. - Sierpinski, Cort (Spring;Art., 2001)
Keywords: dept.art; faculty_collection; sabbatical_report

[Collage and Assemblage Art] - Guagliumi, Arthur (2000)
Keywords: dept.art; faculty_collection; sabbatical_report

Convergence: The Art Collection of the National Academy of Sciences - National Academy of Sciences; Talasek, J. D.; Quinn, Alana (National Academy of Sciences, 2012)
Keywords: Art collections; Catalogs; Catalogs; Science in art; Exhibitions; Art and science; Art; Exhibitions; Natural history; Exhibitions; Nature in art; National Academy of Sciences (U.S.); Pictorial works; dept.art; faculty_collection

Sabbatical Leave Report - Inguanti, Joseph J. (2016)
A study that explores the role of images of the landscape in marketing America to would-be Italian emigrants in the era of the Great Migration (1880-1920).
Keywords: dept.art; faculty_collection; sabbatical_report

Breaking up with Brueghel. - Brownell, Mia (2011)
A sabbatical project, "Breaking up with Brueghel," led to creation of an extensive number of paintings. Their common theme was the correlation between structures of life as depicted in molecular imaging and the structures of art in still life painting. The tradition of food as a subject of still life paintings was re-examined through the genetics of food. The paintings were exhibited in a number of venues, including several abroad, and purchased by donors for various musea and galleries. The accompanying leaflet presents one of the paintings.
Keywords: dept.art; faculty_collection; sabbatical_report

Landscapes of Order, Landscapes of Memory: Italian-American Residential Landscapes of New York Metropolitian Region - Inguanti, Joseph J. (Italian Folk: Vernacular Culture in Italian-American Lives, 2011)
Keywords: Folklore; Italian Americans; Italian Americans; Social life and customs; dept.art; faculty_collection

Medieval Renaissance Baroque: A Cat's Cradle for Marilyn Aronberg Lavin - Lavin, Marilyn Aronberg; Levine, David A.; Freiberg, Jack (Italica Press, 2010)
"Reflects Marilyn Aronberg Lavin's innovative work in art and cultural history in both the print and digital realms. Contributors: Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, Gary Schwartz. Seventy-seven illustrations, bibliography of Lavin's works, index"–Provided by publisher.
Keywords: Art; European; dept.art; faculty_collection

Casablanca on the Moon - Phelan, William R. (Createspace, 2010)
Keywords: dept.art; faculty_collection

Icons, Crosses & Eggs: The Soul and Culture of the Eastern Christian Faith. - Klancko, Robert John; Klancko, Yvonne Shia; Southern Connecticut State University (Southern Connecticut State University, 2009)
Keywords: Art; Europe; Eastern; Exhibitions; Exhibitions; Christian art and symbolism; Exhibitions; Folk art; Orthodox Eastern Church; dept.art; faculty_collection

Light Du Jour (light of the Day) - Phelan, William R. (Createspace, 2009)
Keywords: dept.art; faculty_collection

Easter Eggs & Art: The Robert J. and Yvonne S. Klancko Collection Presented by the Knights of Columbus Museum - Klancko, Robert J.; Klancko, Yvonne S. (Knights of Columbus Museum, 2006)
Keywords: Art collections; Europe; Eastern; Exhibitions; Exhibitions; Christian art and symbolism; Exhibitions; Easter eggs; Exhibitions; Egg decoration; Exhibitions; Folk art; Exhibitions; Klancko; Yvonne S; Klancko; Robert J; dept.art; faculty_collection

100 Creative Drawing Ideas - Audette, Anna Held (Shambhala, 2004)
Keywords: Drawing; Technique; dept.art; faculty_collection

Louis C. Tiffany: The Collected Works of Robert Koch. - Koch, Robert (Schiffer Pub., 2001)
Keywords: Art nouveau; Catalogs; Catalogs; Art glass; Catalogs; Decoration and ornament; Collectors and collecting; History; Glassware; Tiffany; Louis Comfort; 1848-1933; Tiffany Studios (New York; N.Y.); United States; dept.art; faculty_collection

Sabbatical Leave 2018-19 Follow-up Report. - Brownell, Mia (2019)
Two term sabbatical to create "Baroque Float", an extensive number of paintings investigating the visual and conceptual correlation between the structures of life as depicted by scientific molecular/cell imaging and structures of art as depicted by still life and Baroque ceiling painting.
Keywords: dept.art; faculty_collection; sabbatical_report

Multilingual learners, the arts, and family engagement in our public schools - Sawyer, Julie; Luciani, Lauren; Bastiaanse-Fritch, Nicole; Gagne, Shannon; Parsons, Cindy (International Multilingual Research Journal, 2022)
Multilingual learners, some of whom are also new immigrants to the United States, are a growing demographic in our K-12 public schools. Unfortunately, multilingual learners find limited academic opportunities in our public schools. This research explores the opportunity gap for our culturally and linguistically diverse students, the positionality of art educators and their capacity to create interdisciplinary connections with their colleagues, and the power of those collaborations. This study focuses on this work in three different Connecticut districts at the elementary and secondary levels. Student artwork, reflections, community exhibits, and the connections of parents and families with the greater community attest to the power of this promising practice in promoting linguistic democracy in our public schools.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/19313152.2022.2081285
Keywords: English language learners; English learners; Multilingual learners; classroom practices; collaboration; dept.art; instructional strategies; interdisciplinary; partnerships; peer-reviewed; social capital; the arts; visual art

Visual Culture Art Education to Cultivate Critical Racial Consciousness - Bode, Patty (Art Education, 2022)
1 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/00043125.2022.2027724
Keywords: dept.art; peer-reviewed

Picturing France in the fifteenth century: The map in BNF MS Fr. 4991 - Serchuk, C. (Imago Mundi, 2006)
A map of France is included in a manuscript, dated to around 1460, entitled A tous nobles, which contains a historical account and genealogy of the French kings. The map was produced in the wake of the Hundred Years War, when conflict with the English challenged both French identity and territory. The map, however, smooths over a century of war to reveal a nation both strong and independent. Through the mapmaker's selection of places, and his use of fluvial boundaries to define the area concerned, he has created an image of France shaped by ideology and history that is wholly in keeping with its location in the manuscript, where the renaming of Gaul as France is described. The map reveals the territory of France to be a critical link between the mythical past and the political present. This connection between history and territory, also reiterated in the text itself, is presented in a graphic format that may be related to contemporary practice of using maps along with legal documents in the resolution of territorial disputes. Seen in the light of the king's claim to the lands ruled by his ancestors, the map thus constitutes a rare medieval example of French national identity expressed in relation to French territory. © 2006 Imago Mundi Ltd.
5 citations (Crossref) [2023-10-31]
Keywords: A tous nobles; Aquitaine; Bibliothèque nationale de France MS Fr. 4991; Burgundy; Catherine de Medici; Charles IV; Charles VII; Edward III; Eurasia; Europe; France; Genealogy; Hundred Years War; Jean Boutillier; Litigation; Manuscript illumination; Map signs; Map structure; Marcomir; National identity; Nicolas de Nicolay; Philip VI; Propaganda; Western Europe; dept.art; historical cartography; ideology; map; map graphics

Invisibility of Blackness: Visual Responses of Kerry James Marshall - Whitehead, J.L. (Art Education, 2009)
1 citations (Crossref) [2023-10-31]
Keywords: dept.art; peer-reviewed

Landscapes of order, landscapes of memory: Italian-American residential landscapes of the New York metropolitan region - Inguanti, J.J. (Italian Folk: Vernacular Culture in Italian-American Lives, 2010)
In June of 2004, The New York Times reported that the fig trees in the Carroll Gardens section of Brooklyn were dying.1 Accompanying this horticultural death was another transition. Like the fig trees, the elderly Italian-American people who tended them were also gradually disappearing from the neighborhood. The article demonstrated what most residents of the New York tri-state area already knew: The ethnic make-up of a neighborhood often may be "read" through the residential landscape choices of its inhabitants. For people of Italian descent, the fig tree (Ficus carica) is one of many ethnically significant components of the landscape. Throughout the New York City metropolitan region, the residential landscape plays a prominent role in the construction of Italian-American identity. With their symmetrical plans, sheared shrubs, religious statues, and fig trees, Italian-American landscapes proclaim the ethnicity of homeowners and knit neighborhoods together with a shared horticultural and design idiom. Despite the facility with which the denizens of the New York tri-state region discern and describe this "Italian look," no study concerned primarily with the visual analysis and historical precedents of these Italian-American residential landscapes yet exists. Copyright © 2011 Fordham University Press. All rights reserved.
Journal Abbreviation: Ital. Folk: Vernac. Culture in Ital.-Amer. Lives
Keywords: dept.art

Gaul undivided: Cartography, geography and identity in france at the time of the hundred years war - Serchuk, C. (Mapping Medieval Geographies: Geographical Encounters in the Latin West and Beyond, 300-1600, 2014)
Gallia est omnis divisa in partes tres. ‘All Gaul is divided into three parts.’ The opening passages of Julius Caesar’s Commentaries on the Gallic Wars define the target of Roman conquest in geographic terms. Caesar goes on to describe the boundaries of Gaul, its inhabitants, and their character. He does so – at least in part – to enhance the value and importance of his military triumph. The heirs to the vanquished Gauls – French medieval readers and translators of the Gallic Wars – consumed, copied and transformed Caesar’s text, preserving some features and emphasizing them, while erasing others. Although the text and its description of the divisions of Gaul enjoyed considerable popularity and influence in France throughout the Middle Ages, at the time of the Hundred Years War, when France was politically divided, French texts often replaced the tripartite form of Caesar’s Gaul with other models of geographical description. This essay will consider the changing character of geographical thinking about France by the French in the later Middle Ages – expressed in languages both visual and verbal. It will show how geography became entwined with contemporary French identity, particularly with reference to the ways that authors, artists and mapmakers received, transmitted and ignored the tradition of Caesar’s divided Gaul. Fought with the English, primarily on French soil, the war occasioned monumental division in France. Instigated by a dispute about the inheritance of the French crown, as well as over feudal rights owed the French king by his English rival, the Hundred Years War waxed and waned from 1337 to 1453. The calamities of the war were visited on France both physically, in terms of lost and plundered territory, and politically, in terms of the huge rifts that the war wrought in the fabric of French society. Not only did the French struggle against the English, but also, because of bickering, rivalry and ultimately murder among the peers of the realm, the French were also divided against one another, and thus the Hundred Years War also became a civil war. The Armagnacs (French supporters of the French king Charles VII), the Burgundians (French but for some critical years supporting the English) and the English divided France into three fractious parts that joined into fragile alliances. As divisions, they were not as coherent or distinct as Caesar’s provinces, but they divided France painfully if temporarily. © Cambridge University Press 2013.
Journal Abbreviation: Mapp. Medieval Geographies: Geographical Encounters in the Lat. West and Beyond, 300-1600
Keywords: dept.art

Online or face to face?: Instructional strategies for improving learning outcomes in e-learning - Ter-Stepanian, A. (International Journal of Technology, Knowledge and Society, 2012)
The author argues that the online environment lends opportunities for development of critical thinking and creation of a collaborative learning environment not available in the face-to-face classroom. The author compares student participation, test results, the quality of writing assignments in art history survey courses she taught online and face to face at the same university. Not only can critical thinking be encouraged and facilitated by introducing challenging and intriguing topics in group discussions and blogs, but the specific nature of online communication provides a unique and positive atmosphere for discussion: anonymity fosters participation among students who are less fond of public speaking, schedule flexibility means students can do research before posting to discussion boards, a lack of time constraints means discussions do not have to "end" when "class" is over, visibility of discussion postings to the entire class means that students can and do learn from their peers, and the variety of available tools means students can incorporate images, audio/video clips and graphics into their analytical reflections. This paper summarizes the most effective approaches taken to establishing group discussions in asynchronous online courses, discusses learner engagement strategies in the e-learning environment, describes best practices for the optimal use of discussion boards, analyzes learning outcomes of discussion board assignments compared to in-class essays and writing assignments. Copyright © 2012, Common Ground.
3 citations (Crossref) [2023-10-31]
Keywords: Art History; Discussion Forums; Online Instructional Design; dept.art

Familiar voices and the need for reform - Connors, K.E. (Real-World Readings in Art Education: Things Your Professor Never Told You, 2000)
Journal Abbreviation: Real-World Read. in Art Educ.: Things Your Prof. Never Told You
Keywords: dept.art

Rupture - Mickens, A. (Equity and Excellence in Education, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.art; peer-reviewed

The mock (paradoxical, ironic) encomium and the visual arts - Feigenbaum, Gail; Levine, David A. (RSA 2020 Philadephia, 2021)
Keywords: dept.art

Technological frontiers: Design incubation colloquium 6.2 - Girard, Alex; Wong, Daniel J.; Landa, Robin (2020)
Keywords: dept.art; ⛔ No DOI found

Are we ashamed of our children? - Schumacher, NC (Journal of Intellectual Disability Research, 2004)
tex.eissn: 1365-2788 tex.unique-id: ISI:000221695300394
Keywords: dept.art; ⛔ No DOI found

Theorizing experience: four women artists of color - Whitehead, Jessie L (Studies in Art Education: A Journal of Issues and Research in Art Education, 2008)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-903-782-754-32X tex.type: [object Object]
Keywords: dept.art

Ceste figure contient tout le royaulme de France. Cartography and national identity in France at the end of the Hundred Years War - Serchuk, Camille (Journal of Medieval History, 2007)
This paper examines a little known map of France made around the middle of the fifteenth century, for a genealogical manuscript of the text known as A tous nobles, conserved today as Bibliothèque nationale de France [BnF] MS fr. 4991. It argues that the map's prominence in the manuscript articulates a notion of French identity based on a bond to the territory of France rather than on fealty to its king. Using other images from the manuscript, it considers the importance of geography to the emergence of French national sentiment at the time of the Hundred Years War. © 2007 Elsevier Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-140-123-972-806 tex.type: [object Object]
Keywords: A tous nobles; Bibliotheque nationale de France MS fr. 4991; Débat des hérauts d'armes de France et d'Angleterre; Evesham Map; Geography; Grandes Chroniques de France; Marcomir; Medieval cartography; National identity; Norman Conquest; Polemical literature; Remanieurs; dept.art

Siate Felici: Garden imagery in a Messinese Biancheria di Letto, c. 1900 - Inguanti, Joseph J. (Embroidered Stories: Interpreting Women's Domestic Needlework from the Italian Diaspora, 2014)
For Italian immigrants and their descendants, needlework represents a marker of identity, a cultural touchstone as powerful as pasta and Neapolitan music. Out of the artifacts of their memory and imagination, Italian immigrants and their descendants used embroidering, sewing, knitting, and crocheting to help define who they were and who they have become. This book is an interdisciplinary collection of creative work by authors of Italian origin and academic essays. The creative works from thirty-seven contributors include memoir, poetry, and visual arts while the collection as a whole explores a multitude of experiences about and approaches to needlework and immigration from a transnational perspective, spanning the late nineteenth century to the late twentieth century. At the center of the book, over thirty illustrations represent Italian immigrant women's needlework. The text reveals the many processes by which a simple object, or even the memory of that object, becomes something else through literary, visual, performance, ethnographic, or critical reimagining. While primarily concerned with interpretations of needlework rather than the needlework itself, the editors and contributors to Embroidered Stories remain mindful of its history and its associated cultural values, which Italian immigrants brought with them to the United States, Canada, Australia, and Argentina and passed on to their descendants.
Keywords: dept.art

The convergence of critical pedagogy with arts-based service-learning - Alexander, Amanda; Schlemmer, Ross H (Convergence of Contemporary Art, Visual Culture, and Global Civic Engagement, 2016)
Neoliberal globalization and politics are reshaping the landscape in the United States and other countries; consequently, broader and more critical perspectives about education, community, and the arts are becoming increasingly more important. In the field of education, critical pedagogy has become a philosophy to expose, critique, and challenge neoliberal free market capitalism. Critical pedagogy becomes the link between local and global perspectives that reveals conditions of social and cultural injustices. Through socially engaged art education and service-learning initiatives, the authors have been engaging their students to become actively engaged citizens. This chapter offers a qualitative critique of the authors' own pedagogical practices through the convergence of critical pedagogy and arts-based service-learning by applying, adapting, and revising existing models of critical pedagogy such as Cipolle's (2010) “four elements of critical consciousness development” (p. 40) and Shor's (1992) methods for implementing critical pedagogy.
Citation Key Alias: lens.org/155-893-139-768-359
Keywords: dept.art

The world for a king: pierre desceliers’ map of 1550. by chet van duzer - Serchuk, Camille (Imago Mundi, 2016)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/133-136-133-366-651 tex.type: [object Object]
Keywords: dept.art

The Dutch Encounter with Italy - Levine, David A. (The Ashgate Research Companion to Dutch Art of the Seventeenth Century, 2016)
Keywords: dept.art

Discussion board assignments and their impact on creating engaged learning environments in art history online courses - Ter-Stepanian, Anahit (Handbook of Research on Didactic Strategies and Technologies for Education: Incorporating Advancements, 2013)
The adaptation of traditional, face-to-face courses to the online format presents both challenges and opportunities. Many pedagogical practices need to be rethought when designing online courses. A successful online course needs to be intellectually stimulating and engaging. The chapter demonstrates how to create an engaging learning environment without any additional budget. The author describes approaches that she has developed, experimented with, and found to be effective in asynchronous online art history courses, as well as learner engagement strategies she has implemented in the eLearning environment. Advantages of scenario-based discussions board assignments and the effects of role playing in discussion forums are discussed. The author shares examples of personalized discussion board assignments aimed to motivate online learners, create a collaborative learning environment, improve peer-to-peer interaction, and prevent plagiarism.
Keywords: dept.art

Parody, Proverb, and Paradox in Two Late Works by Pieter Bruegel the Elder - Levine, David A. (Parody and Festivity in Early Modern Art, 2012)
Keywords: dept.art

Frans Hals and the Vernacular - Levine, David A. (The Transformation of Vernacular Expression in Early Modern Arts, 2011)
"Frans Hals and the Vernacular" published on 01 Jan 2012 by Brill.
Keywords: dept.art

Medieval Renaissance Baroque: A Cat's Cradle in Honor of Marilyn Aronberg Lavin - Levine, David A.; Freiberg, Jack (Italica Press, Inc., 2010)
"Medieval renaissance Baroque" celebrates Marilyn Aronberg Lavin's breakthrough achievements in both the print and digital realms of art and cultural history. Fifteen friends and colleagues present tributes and essays that reflect every facet of this renowned scholar's brilliant career. Tribute presenters include Ellen Burstyn, Langdon Hammer, Phyllis Lambert, and James Marrow. Contributors include Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, and Gary Schwartz. 79 illustrations, bibliography of Marilyn Lavin's works, index.
Keywords: dept.art

“Urbs Aeterna” and Dutch Painting of Roman Ruins - Levine, David A. (Medieval Renaissance Baroque: a cat's cradle for Marilyn Aronberg Lavin, 2010)
"Reflects Marilyn Aronberg Lavin's innovative work in art and cultural history in both the print and digital realms. Contributors: Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, Gary Schwartz. Seventy-seven illustrations, bibliography of Lavin's works, index"–Provided by publisher.
OCLC: 423389186
Keywords: dept.art

Around the world: Borders and frames in two sixteenth-century Norman map books - Serchuk, Camille (Maps and Travel in the Middle Ages and the Early Modern Period, 2019)
Keywords: dept.art

Geospatial sculpture: Nonverbal communication through the tactilization of geospatial data - Heidkamp, C. Patrick; Slomba, Jeffrey T. (GeoHumanities, 2017)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-225-748-349-137, pop00234
Keywords: 3D visualization; Connecticut; Escultura Geoespacial; GeoSpatial Sculpture; dept.art; dept.egm; geografías no verbales; nonverbal geographies; peer-reviewed; tactilización; tactilization; visualización en 3D; 三维可视化; 地理空间雕塑; 康涅狄格; 触觉化; 非语言的地理

Socially engaged art education: practices, processes, and possibilities - Schlemmer, Ross H.; Carpenter, B. Stephen; Hitchcock, Erika (Art Education, 2017)
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00121
Keywords: dept.art; peer-reviewed

Jan Miense Molenaer’s 'Boys with Dwarfs' and the heroic tradition of art - Levine, David A. (The primacy of the image in northern European art, 1400-1700, 2017)
Keywords: dept.art

Socially engaged art education: defining and defending the practice - Schlemmer, Ross H (Handbook of Research on the Facilitation of Civic Engagement through Community Art, 2017)
Community Arts have a long history within art and education, yet its practices continue to evolve. The issue of nomenclature when discussing such socially engaged practices raises the deeper questions of whether work in this area suggests the formalization of yet another new genre of art, or does it entail a more profound re-ordering of the discursive system that underlies most existing modes of artistic production? This chapter attends to individual differences and similarities in perception and practice through a careful consideration for how the field of art education might nurture new and diverse articulations of community-based practices that emphasize relational aesthetics, participatory pedagogy, and socially engaged artistic practices. This chapter will (re)frame the discourse as Socially Engaged Art Education (SEAE) to emphasize a new terrain of consciousness that is socially responsible and ethically sound, and goes beyond mere promotion of aesthetic quality to contribute to improved quality of life.
Citation Key Alias: lens.org/014-957-936-013-626
Keywords: dept.art